P19 Socioeconomic disparities in trajectories of adiposity across childhood. (16th November 2010) - Howe, L D; Tilling, K; Galobardes, B; Smith, G Davey; Ness, A R; Lawlor, D A
Abstract : Objective: Socioeconomic inequalities in obesity are consistently observed in high-income countries, with lower socioeconomic groups tending to be more adipose amongst both adults and children. The development of such inequalities across childhood, however, has not been studied using longitudinal data. Design: Using longitudinal data from a prospective birth cohort study, we modelled individual trajectories of adiposity from birth to 10 years using random effects linear spline models, and estimated differences in trajectories by socioeconomic position (measured by maternal education). Trajectories were modelled separately for boys and girls. Setting: Avon Longitudinal Study of Parents and Children, South West England. Participants: Participants were born in 1991/1992. Main Outcome Measure: Ponderal index (PI, kg/m 3, N=12 246) from birth to 2 years and body mass index (BMI, kg/m 2, N=11 380) from 2 to 10 years. Height and weight measures were from research clinics, health records, and parent-completed questionnaires; trajectory models included an indicator of measurement source to account for reduced accuracy of parent-reported measurements. Results: There was little socioeconomic patterning of PI from birth to 2 years. Socioeconomic differences in BMI began to emerge by 4 years old, and widened with increasing age. Amongst girls there was a clear gradient across all categories of maternal education by age 8, with daughters of more educated women being less adipose. Amongst boys, sons of degree educated women had lower BMI, but there was little difference between the three lower maternal education categories. By 10 years old the mean BMI difference between the highest and lowest education category was 0.38 kg/m 2 for boys and 0.89 kg/m 2 for girls. The results imply that interventions to prevent inequalities in childhood obesity should begin in pre-school years.